THE MODELS OF CALCULATION OF EXTERNAL COST FROM ROAD TRAFFIC ACCIDENTS - Jiří Alina (Perner’s Contacts, 2013)
Road traffic accidents are serious public problem that encroaches whole society. Primarily the impact of traffic accident experiences straight forward participants of accident. In another sequence impacts and most of all costs are accepted by the whole society. Costs connected with road traffic accidents are estimated beyond 2 - 4 % the gross domestic product in general. It is absolutely necessary to try to determine level of costs, analyse the impacts and consequently possible chances for improvement of situation. The consequences of traffic accidents can be horrendous, and people indicate a high willingness-to-pay (WTP) to reduce the risk of being a victim of a traffic accident. Road traffic accidents impacts and their evaluations can be primarily divided into two parts: direct and indirect impacts. Very often is calculation (models) of external cost based on the value of statistical life (VOSL). The aim of this paper is to present models for calculation of accident costs which is used in the EU member states.